Kebijakan Penataan Pedagang Kaki Lima dan Penertibannya oleh Satpol PP Di Wilayah Kabupaten Boyolali - M Julianto; Adhiputro Pangarso Wicaksono; Ananda Megha Wiedhar Saputri (Jurnal Bedah Hukum, 2021)
vendors (PKL) are a common phenomenon that occurs in big cities in Indonesia. The case of street vendors is considered by many parties as a form of government failure in providing job opportunities for the poor. Boyolali City is one of the cities which is alsStreeo inhabited by street vendors. This research was conducted using an empirical juridical approach, the authors went to the field to make observations and direct interviews with research informants. There are two formulations of the problem in writing this thesis, namely: (1). How is the policy of controlling street vendors in the Boyolali district, and the second (2). What are the suporting and inhibiting factor in controlling street vendors in the Boyolali area. The structuring policy by the Boyolali city government is appropriate and in accordance with the Boyolali regional regulation Number 18 of 2016 concerning the arrangement and empowerment of street vendors. The control carried out by the Satpol PP is also in accordance with PP number 6 of 2010